1993
DOI: 10.1002/ijc.2910550411
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin expression in head and neck squamous‐cell carcinoma is associated with clinical outcome

Abstract: The cell-cell adhesion molecule E-cadherin has been shown to suppress invasive growth of epithelial cells in vitro, and loss of its expression is thought to be important in invasion and metastatic potential of epithelial tumors in vivo. We retrospectively studied the level of E-cadherin expression in 50 primary head and neck squamous-cell carcinomas (HNSCC) by immunohistochemical methods, on frozen sections, using anti-E-cadherin monoclonal antibody (MAb) 6F9. It concerned patients with different stages of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
105
6
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 10 publications
10
105
6
8
Order By: Relevance
“…The cell-cell adhesion molecule E-cadherin suppresses invasive growth of epithelial cells in vitro. Loss of expression is important in lymph node metastasis (28), leading to poor prognosis in oral SCC (28,29). In this study, the downregulation of E-cadherin expression in oral SCC correlated with increased lymph node metastasis (P=0.023) and poorer prognosis (P=0.0146), as seen in previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…The cell-cell adhesion molecule E-cadherin suppresses invasive growth of epithelial cells in vitro. Loss of expression is important in lymph node metastasis (28), leading to poor prognosis in oral SCC (28,29). In this study, the downregulation of E-cadherin expression in oral SCC correlated with increased lymph node metastasis (P=0.023) and poorer prognosis (P=0.0146), as seen in previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…However, it was not an independent prognostic factor in the disease-specific survival analysis. Mattijssen et al (1993) studied the level of E-cadherin expression in primary head and neck squamous-cell carcinomas. They reported a significant correlation between the level of E-cadherin expression in the primary tumor and the degree of differentiation, and no relation was found with tumor size or regional lymph-node classification.…”
Section: Figure 3 A) the Staining Of Normal Epithelial Tissue For E-mentioning
confidence: 99%
“…Changes or alteration in the function and expression of the cell to cell adhesion molecule, Ecadherin, a-catenin and b-catenin, have been postulated to be an early event in the multiple process of tumour metastasis and an important factor in tumour progression (Birchmeier et al, 1993;Ponta et al, 1994). A variety of studies regarding the relationship between the expression of E-cadherin, a-catenin, b-catenin and the existence of lymph node metastasis in human cancers have been performed and some authors found a significant correlation (Sato et al, 1999;Zheng et al, 1999), while others did not (Mattijssen et al, 1993;Andrews et al, 1997).…”
mentioning
confidence: 99%